PENGARUH MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI SMA NEGERI 1 MONTASIK - Nurfadhillah, Lilis; Mustofa, Achmad; Anggraini, Irma (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2025)
The Discovery Learning learning model is a learning approach that allows students to discover concepts and principles independently through a process of investigation and experimentation. The problem in this study is the low student learning outcomes in economics subjects at SMA Negeri 1 Montasik. The purpose of this study was to determine student learning outcomes before and after the implementation of the Discovery Learning learning model and to determine student responses to the implementation of the Discovery Learning learning model in economics subjects at SMA Negeri 1 Montasik, Aceh Besar Regency. This study uses a quantitative approach and this type of research is experimental with a One-Group pretest-posttest design. The population used in this study were all 33 students of class X-3 of SMA Negeri 1 Montasik, with a sampling technique using total sampling. Data collection techniques were carried out by learning outcome tests, student response questionnaires and documentation. The results showed that the average value of student learning before using the Discovery Learning learning model (pretest) obtained a value of 44.24 and after the application of the model (posttest) increased to 82.72. Based on the results of the Wilcoxon Signed Ranks Test, a significance value (Asymp. Sig. 2-tailed) of 0.000 > 0.05 was obtained, indicating a significant difference between the pretest and posttest results. Therefore, it can be concluded that there is a significant difference between the pretest and posttest scores. This means that the treatment or intervention given before the posttest has an impact on increasing or decreasing the participants' scores. Because the Z value is negative and based on negative ranks, this indicates that the posttest scores are generally higher than the pretest scores, indicating an increase after the treatment.